Computed Tomography Enterography: Better Luminal Distension with a Shorter Ingestion Time Protocol in an Indian Population - R., Ambika; Reddy, Vidhya Rani (Journal of Gastrointestinal and Abdominal Radiology, 2018)
Aim This article prospectively evaluates the adequacy of bowel distension in computed tomography enterography (CTE) with a 45-minute contrast ingestion time and compares it with the most widely used protocol in the literature of 1 hour 20 minutes.Materials and Methods The CTE was performed in 42 consecutive patients divided into two groups—A and B. Group A patients were instructed to drink 2 L of polyethylene glycol electrolyte solution over 1 hour 20 minutes. Group B patients were instructed to do the same over 45 minutes. At the end of contrast ingestion, plain and contrast CT abdomen was performed and CTE images were reviewed. Manual quantitative analysis of degree of small bowel distension was performed in the following manner: on coronal images, the abdominal cavity was divided into four quadrants: right upper, left upper, right lower, and left lower quadrants. The maximum small bowel lumen diameter (inner-to-inner wall) was measured in five different loops within each of the four quadrants. If four or more measurements in a quadrant ≥ 1.8 cm (considered “adequate luminal distension”), a score of 1 was assigned to that quadrant. If less than 4 measurements in the quadrant > 1.8 cm, a score of 0 was assigned to that quadrant. The ensuing sum of scores from all four quadrants resulted in the distension grade for that CTE study (Grades 1–4).Results There was a statistically significant difference in the degree of small bowel distension between the two groups with better distension seen in group B (p < 0.001).Conclusion Indians have a rapid gut transit time compared with Western populations. Hence, CTE contrast ingestion time protocols optimized in Western populations may not be suitable in Indians. The shorter 45-minute ingestion protocol provided consistently better luminal distension in our population than the longer 1 hour 20-minute protocol described in the literature. To the best of our knowledge, there are no other studies comparing CTE ingestion time protocols in a given population.
Keywords: computed tomography enterography; gut transit time; oral contrast ingestion time; polyethylene glycol